Using local knowledge to assess the sustainability of groundwater resources: applying the social-ecological systems framework to the Hamedan-Bahar Plain, Iran - Taraneh Sarami Foroushani; Hamid Balali; Reza Movahedi; Stefan Partelow (ZBW - Leibniz Information Centre for Economics, 2024)
Sustainable access to groundwater remains a key challenge for local users, managers and policy makers, particularly in arid agricultural regions such as Iran. Identifying and assessing the status of diverse sustainability indicators using local knowledge can act as a step in the right direction for often invisible and hard to measure resources, especially when developed through inclusive approaches that include expert stakeholder inputs. In this article, we apply Ostrom's social-ecological systems framework (SESF) to assess how the local knowledge of key informant stakeholders can be used to assess the sustainability of groundwater resources on the Hamadan-Bahar plain in Iran. We evaluate the importance of each of the SESF's first-tier variables based on 52 indicators attained from literature review and expert insights. Local knowledge is used to assess the sustainability status of each indicator through a survey of 22 key informants. For data analysis, we use the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) and the Shannon Entropy methodologies to weight and rank indicators based on the data provided on their influence on sustainability. Findings suggest that the Resource System (RS) and Resource Unit (RU) indicators have the most positive influence on sustainability. In contrast, the Governance System (GS), Actor (A) and Interaction (I) first-tier variables were evaluated as less stable, along with Outcomes (O). This suggests that social factors and diverse outcomes may need further attention in the region to ensure management and policy development that can better enable sustainable outcomes. This analysis also demonstrates the usefulness of a comprehensive science-based framework for organizing, analyzing and presenting a wide range of complex information to inform policymakers and planners.
Keywords: 330; Groundwater management; local knowledge; knowledge co-production; sustainability indicators; socio-ecological systems (SES); stakeholder inclusion; water governance; commons